Differentiated Approach to Surgical Treatment of Cholelithiasis Complicated by Choleducholithiasis and Obstructive Jaundice - Aliya M. Aitbayeva (Journal of Global Pharma Technology, 2019)
This study contributes to solving problems of steady increase in cholelithiasis incidence with high percentage of associated complications, high mortality rate and unsatisfactory outcomes. This study rises from universally recorded increase in the incidence of gallstones, from the prevalence of complicated disease forms, from high mortality rate and unsatisfactory treatment outcomes. This study aims to improve the outcomes of surgical treatment in patients with complicated cholelithiasis who underwent a differentiated surgical intervention. This study analyses treatment outcomes in 140 patients who undergone surgery for cholelithiasis complicated by choledocholithiasis and obstructive jaundice. Patients underwent surgical interventions in a clinical unit under the West Kazakhstan Marat Ospanov State Medical University in 2014/2018. The findings show that a surgical approach towards the treatment of patients via minimally invasive surgery should depend on the severity of obstructive jaundice. Postoperative complications were found in 7.8% of patients in the main group, and the death rate was 1.1%. By contrast, in the control group, 32% had postoperative complications and the death rate was 4%. If differentiated, minimally invasive surgical treatment of cholelithiasis complicated by choledocholithiasis and obstructive jaundice allows avoiding serious complications when correcting abnormalities in the biliary system via traditional laparotomy with a wide incision. These findings suggest that a differentiated approach can significantly improve treatment outcomes in patients with cholelithiasis complicated by choleducholithiasis and obstructive jaundice.Keywords: Cholelithiasis, Choledocholithiasis, Obstructive jaundice, Endoscopic interventions.